Mesin Cuci Tangan Portable Otomatis - Arham Arifin (Celebes Computer Science Journal, 2020)
Covid-19 is a virus that can adhere to various surfaces of objects. One of the causes of someone contracting the Covid-19 virus is by touching the face, namely the nose and eyes, where the hand has previously touched objects or surfaces that have been infected with the Covid-19 virus. These problems are our advocates for making a portable automatic hand washing machine. This solution is considered important to overcome the spread of the Covid-19 virus through the touch of a hand. In general, the work of the system is to drain water and soap from the faucet automatically and alternately with the trigger is the hand reading by the proximity sensor. The working sequence is water first, then liquid soap, then water again and after that the hands can be dried by means of an automatic hand dryer blower. The hand washing machine that we make is protable and automatic which can be moved easily from one place to another, this allows it to be placed in a room that may be difficult to get to or far from a water source, because in this tool there is a water reservoir.